1994
DOI: 10.1007/bf01952862
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, copper and selenium in reproduction

Abstract: Of the nine biological trace elements, zinc, copper and selenium are important in reproduction in males and females. Zinc content is high in the adult testis, and the prostate has a higher concentration of zinc than any other organ of the body. Zinc deficiency first impairs angiotensin converting enzyme (ACE) activity, and this in turn leads to depletion of testosterone and inhibition of spermatogenesis. Defects in spermatozoa are frequently observed in the zinc-deficient rat. Zinc is thought to help to extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
191
0
9

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(210 citation statements)
references
References 229 publications
10
191
0
9
Order By: Relevance
“…Zinc acts as a co-factor for enzymes promoting DNA transcription and protein synthesis [32], has a role in expression of steroid hormone receptors [33] and has anti-apoptotic [34] and anti-oxidant properties [35]. Studies have demonstrated that a zinc deficiency can lead to subfertility and abnormal reproductive outcomes [36], and to pregnancy complications [37,38]. However, previous studies have failed to confirm a role for zinc in human infertility or the response to fertility treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc acts as a co-factor for enzymes promoting DNA transcription and protein synthesis [32], has a role in expression of steroid hormone receptors [33] and has anti-apoptotic [34] and anti-oxidant properties [35]. Studies have demonstrated that a zinc deficiency can lead to subfertility and abnormal reproductive outcomes [36], and to pregnancy complications [37,38]. However, previous studies have failed to confirm a role for zinc in human infertility or the response to fertility treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc affects different aspects of mammalian reproduction [Dissanayake et al 2009;Björndahl and Kvist 2010]. Low zinc intake by young males of several species including humans, interferes with normal sexual development [Bedwal et al 1991;Saxena et al 1993;Bedwal and Bahuguna 1994;Kaji 2001;Dissanayake et al 2009] and leads to gonadal dysfunction. Zinc also plays an essential role in the synthesis and secretion of luteinizing hormone (LH), follicle-stimulating hormone (FSH) and prolactin, gonadal differentiation, testicular steroidogenesis, and genetic expression of steroid hormone receptors [Bedwal et al 1991;Bedwal and Bahuguna 1994;Ali et al 2007].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Furthermore, zinc, copper and selenium are essential for reproductive processes. 15 Therefore, the ability of the placenta to transfer nutrients and toxicants alike is of concern in relation to foetal development and health. 16 In most cases, the same processes that aid transport of nutrients through the placenta, may also act as the pathways for toxic elements, especially if these have chemical similarities with the nutrient metabolites, or simply because of passive diffusion.…”
Section: Introductionmentioning
confidence: 99%